Sanksi Pidana Perdagangan Perempuan (Women Trafficking) (Studi Komparatif antara Undang-Undang No. 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang dan Hukum Islam) - Q Zaman (Raheema, 2017)
Nowadays, women trafficking has become iceberg phenomenon. The women, in fact, have a great level as well as impact in domestic and social life. However, they are always become victims on human trafficking problem. There are so many factors behind; violence exploitation, sex worker, cyber crime, contract marriage, drugs, and so forth. Furthermore, some modus of crimes are about syariah, like umroh, nikah sirri, etc. Therefore, this case is interesting to be researched deeply. How the punishment of the perpretrators with comparative analysis between UU No. 21/2007 tentang TPPO and Hukum Islam. Moreover, from the literature analysis, it is found that the punishment on UU No. 21/2007 tentang TPPO that the women trafficking practice is a crime and shoould be punished by the law fairly.